Literature Review : Faktor – Faktor Yang Mempengaruhi Kualitas Tidur Pada Lansia - Iis Putri Rambu Padu Leba (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
The quality of sleep in the elderly at night has decreased by about 70% -80% in adulthood. Older people are more likely to experience poor sleep quality due to the aging process. Sleep disturbances in the elderly include difficulty getting to sleep, difficulty maintaining deep sleep and waking up too early. This study aims to analyze articles related to the factors that affect sleep quality in the elderly. The method or design used in this study is a Literature Review by searching for journals using the ProQuest, Google Scholar, and Pubmed databases. The journal criteria used are journals published within the last 5 years. The analysis in this study is synthesized in the form of a narrative. The results of research from 14 journals have been obtained as much as 64.3% using a cross-sectional study design and as many as 42.8% using Chi-Square Test analysis, from the analysis obtained several factors that affect sleep quality in the elderly, including: hypertension, level age, excessive napping, physical activity, emotional stress, depression, loneliness, sleep duration, and drug use. In this study it can be concluded that the factors that affect sleep quality in the elderly are: hypertension, age level, excessive naps, physical activity, emotional stress, depression, loneliness, sleep duration, and use of drugs.